A neuroleptic malignant-like syndrome (NMLS) in a patient with Parkinson’s disease resolved with rotigotine: a case report - Fiore, Stefania; Persichino, Lidia; Anticoli, Sabrina; De Pandis, Maria Francesca (Acta Biomedica Atenei Parmensis, 2014)
Neuroleptic Malignant-Like Syndrome (NMLS) is a rare, but potentially fatal complication of dopaminergic therapy in Parkinson’s disease due to a sudden withdrawal of dopaminergic therapy. Here, we describe the case of a 79 years old woman, with 19 years history of Parkinson disease treated with L-dopa, dopamine agonists and MAO inhibitors, whose sudden withdrawal due to lack of therapeutic compliance, led to sudden onset of high fever, muscle rigidity, akinesia, autonomic dysfunction, impaired level of consciousness, respiratory distress and dysphagia with inability to take oral dopaminergic therapy. High blood levels of CPK and myoglobinaemia were found. The patient was treated with transdermal Rotigotine starting from a dose of 2 mg/24 hours, that was rapidly increased to 6 mg/24 hours, leading to resolution of the acute disturbances.